ShoreScape - Janneke van Bergen (A+BE: Architecture and the Built Environment)
Urbanized sandy shores around the world suffer from coastal erosion due to a lack of sediment input and sea level rise. These dynamics place new demands on coastal spatial planning. To compensate for coastal erosion in a more natural and systemic way, sand nourishments are deployed as a ‘Building with Nature’ technique, restoring the sediment balance and promoting dune formation as coastal defence. In this research, Building with Nature is reframed as a landscape approach, regenerating the coastal landscape by tuning the interactions between the geomorphological, ecological, and urban system, to adapt to sea level rise. To this end, design principles have been developed that integrate nourishment dynamics, natural succession, and adaptive urban design to build towards safe and multi-functional coastal landscapes— Shore-Scapes. They focus on spatial coastal configurations utilizing wind-driven sedimentation processes to build up the coastal buffer, supporting dune formation, multifunctionality, and landscape differentiation. To direct sediment dynamics for coastal reinforcement and landscaping, three subsequent tools for dynamic design have been derived: morphogenesis, dynamic profiling, and aeolian design principles. With these principles, validated by fieldwork, GIS, and computational modelling, spatial arrangements can be composed enhancing the aeolian build-up of the coastal landscape over time. These principles were applied and contextualized in four case studies along the Dutch coast. They illustrate how dunes along urbanized shores can grow naturally after nourishment and allow coastal safety, recreation, and nature to complement each other.